Food Consumers' Satisfaction and Loyalty Regarding the Use of E-Wallets - Anak Agung Istri Arundhati Aiswara; Ketut Budi Susrusa; Gede Mekse Korri Arisena; Ary Bakhtiar (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2026)
This study was conducted to examine the level of satisfaction and loyalty of food consumers regarding the use of e-wallets among students at Universitas Muhammadiyah Malang. The data collection method used was a survey approach involving interviews via a questionnaire administered to 96 respondents who were specifically e-wallet users. The data were analyzed using the Customer Satisfaction Index (CSI), Customer Loyalty Index (CLI), and the Pearson Product Moment correlation test. The results of the study indicate that the frequency of e-wallet use among students is relatively high and has become a daily food shopping activity. However, satisfaction and loyalty levels remain low, with a CSI value of 37.92% (dissatisfied category) and a CLI value of 20.92% (non-loyal category). The main challenges faced by students are limited top-up balances and slow transaction processing. Nevertheless, a significant positive relationship was found between satisfaction and loyalty (r = 0.710), indicating that increased satisfaction can have a direct impact on user loyalty. These findings have important implications for the development of e-wallet services that are more responsive to the needs of young users.